Diversidade taxonômica e funcional das aves da Mata Atlântica sob influência da maior metrópole do hemisfério sul, São Paulo, Brasil - Melo, Marcos Antônio (2021)
Urbanization creates one of the most irreversible forms of land use and occupation. Commonly, urbanization results in species losses and functional homogenization of bird communities, thus affecting the functioning of ecosystems. The objective of this thesis was to understand, in different ways, how the urbanization of São Paulo's megacity influences bird communities and ecological processes. In the first chapter, I evaluated how urban parks and residential areas contribute to the maintenance of bird communities and diversity of ecosystem functions compared to large forest fragments (source areas). The results show the need to maintain large areas of native forest on the city limits to preserve the rich avifauna and maintenance of ecosystem functioning. Urban parks next (<10 km) to the source areas show greater bird’s functional diversity, but not taxonomic, than those far away (> 10 km). Moreover, vegetation complexity can mitigate the impact of urbanization in urban habitats. In the second chapter, I evaluated how bird guilds and the entire community can be influenced by biotic-abiotic characteristics in São Paulo’s urban green areas. The results indicated the importance of large green areas with high shrub cover to shelter rich regional birdlife. On the other hand, small green areas should mitigate the possible negative impacts on birds related to glass panels, vehicle traffic and the presence of humans, dogs and cats, which can systematically eliminate functional groups and decrease the provision of ecosystem services provided by specialist guilds (frugivorous-nectarivorous and insectivorous) and also generalists. In the third chapter, I tested how species, functional groups and functional diversity indices respond to the amount of vegetation (normalized difference vegetation index, NDVI) and red clay roofs (RCR, a potential bird nesting site) in residential areas of the São Paulo megacity. The results indicate that combinations between high coverage of NDVI (> 0.5) and RCR can increase the occurrence of species and ecological functions in Neotropical cities. These results can guide environmental management measures and public policies aimed at the conservation of biodiversity and its ecosystem services (essential to human well-being) in different urban habitats.